2018
DOI: 10.4049/jimmunol.1701442
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Interacts with the CHI3L1 Axis and Contributes to Hermansky–Pudlak Syndrome Lung Disease

Abstract: Hermansky-Pudlak syndrome (HPS) comprises a group of inherited disorders caused by mutations that alter the function of lysosome-related organelles. Pulmonary fibrosis is the major cause of morbidity and mortality in HPS-1 and HPS-4 patients. However, the mechanisms that underlie the exaggerated injury and fibroproliferative repair responses in HPS have not been adequately defined. In particular, although Galectin-3 (Gal-3) is dysregulated in HPS, its roles in the pathogenesis of HPS have not been adequately d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 62 publications
5
32
0
2
Order By: Relevance
“…Recent studies demonstrated that the secreted Chi3L1 directly binds to IL-13 receptor α2 (IL-13Rα2) that was originally described a high affinity receptor for IL-13 and believed to be a decoy receptor for IL-13 [39][40][41][42]. The extracellular interaction between IL-13Rα2 and Chi3L1 regulates pathogen responses, oxidant injury, inflammation, and melanoma metastasis [39], and also Chi3L1 activates the Wnt/β-catenin, mitogen-activated protein kinase (MAPK), and Protein kinase B (PKB/AKT) signaling pathways via IL-13Rα2 [39] In addition, transmembrane protein 219 (TMEM219), a membrane protein plays a critical role in Chi3L1-induced IL-13Rα2 mediated signaling and responses including oxidant-induced apoptosis, lung injury, and melanoma metastasis [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated that the secreted Chi3L1 directly binds to IL-13 receptor α2 (IL-13Rα2) that was originally described a high affinity receptor for IL-13 and believed to be a decoy receptor for IL-13 [39][40][41][42]. The extracellular interaction between IL-13Rα2 and Chi3L1 regulates pathogen responses, oxidant injury, inflammation, and melanoma metastasis [39], and also Chi3L1 activates the Wnt/β-catenin, mitogen-activated protein kinase (MAPK), and Protein kinase B (PKB/AKT) signaling pathways via IL-13Rα2 [39] In addition, transmembrane protein 219 (TMEM219), a membrane protein plays a critical role in Chi3L1-induced IL-13Rα2 mediated signaling and responses including oxidant-induced apoptosis, lung injury, and melanoma metastasis [40].…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular interaction between IL-13Rα2 and Chi3L1 regulates pathogen responses, oxidant injury, inflammation, and melanoma metastasis [39], and also Chi3L1 activates the Wnt/β-catenin, mitogen-activated protein kinase (MAPK), and Protein kinase B (PKB/AKT) signaling pathways via IL-13Rα2 [39] In addition, transmembrane protein 219 (TMEM219), a membrane protein plays a critical role in Chi3L1-induced IL-13Rα2 mediated signaling and responses including oxidant-induced apoptosis, lung injury, and melanoma metastasis [40]. When viewed in combination and based on the previous literatures [39][40][41][43][44][45][46], it is supposed that Chi3L1 is secreted and extracellular Chi3L1 regulates lung metastasis and pathological phenomenon via putative membrane proteins. However, it is still unclear how Chi3L1 accomplishes these varied responses and how Chi3L1 induces lung tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…96 Gal-3 physically interacts with IL-13Rα2 and CHI3L1 to compete with TMEM219 for IL-13Rα2 binding and diminish the anti-apoptotic role of CHI3L1. 31 Upon accumulation in the extracellular space, Gal-3 drives the apoptosis of primary lung epithelial cells. Conversely, the intracellular expression of Gal-3 has a dominating influence on M2 macrophage differentiation and myofibroblast proliferation, thereby contributing to exaggerated injury and fibroproliferative repair responses in Hermansky-Pudlak syndrome (HPS) 31 ( Fig.…”
Section: Galectin-3mentioning
confidence: 99%
“…163 Additionally, CHI3L1 exacerbates HPS-associated pulmonary fibrosis through binding to CRTH2 receptor. 31,97 Serum CHI3L1 levels are also increased in patients with cystic fibrosis 164 as well as asbestosis. 165 Chronic obstructive pulmonary disease (COPD) CHI3L1 is upregulated in COPD, 166,167 in which it may contribute to tissue inflammation and remodeling by sustaining the synthesis of proinflammatory and fibrogenic chemokines and of metalloproteinases by alveolar macrophages.…”
Section: Respiratory Diseases Inflammationmentioning
confidence: 99%
“…Both of these factors activate alveolar macrophages to hypersecrete additional chemokines, inflammatory cytokines and TGFβ, all of which contribute to AT2 apoptosis and fibrotic macrophage infiltration . Increased circulating levels of galectin‐3 and of chitinase 3‐like‐1 protein, a cytokine that stimulates fibroproliferative repair in the lung, also contribute to enhanced fibrosis and AT2 apoptosis . The molecular mechanisms by which BLOC‐3 or its target Rabs might enhance chemokine secretion by AT2 cells are not clear, but recent development of an HPS1 model in an AT2 cell line that recapitulates phenotypes of primary AT2 cells, including increased MCP‐1 production, will likely accelerate discovery in this area.…”
Section: Hps‐associated Protein Complexesmentioning
confidence: 99%